Genomic study of Photobacterium marinum strain J15 and development of genome scale metabolic model for cellular metabolism identification - Roslan, Noordiyanah Nadhirah (2017)
Photobacterium sp. strain J15 was originally isolated from marine water of Tanjung Pelepas, Johor. It was initially studied for its novel GDSL esterase and asparaginase production. With the production of the potential enzymes and secondary metabolites, it was realised that little is known about the general metabolism of this Photobacterium genus. Therefore, the aim of this study was to provide an understanding of cellular metabolism of strain J15 through genomics and phenomics analysis and characterization of the genome-scale properties. Genome scale metabolic model was also constructed in order to enhance the understanding of the cell’s organization and its functionality as a whole. In this study, the genome sequence of Photobacterium sp. strain J15 was determined using PacBio sequencing. The genome contained 5,684,538 base pairs comprised 3 contigs; 2 chromosomes and 1 plasmid. A total of 4,924 open reading frames (ORFs) were predicted and 4,811 proteins were annotated against NCBI database. There are altogether 3,238 proteins with GO assignment and 874 proteins assigned to KEGG pathways. Phylogenomics analysis showed that Photobacterium sp. strain J15 is indeed the same species with P. marinum AK15. There were 535 subsystems represented in the draft genome scale metabolic model (GEM) of P. marinum J15. The iSS1110 model consists of 1110 genes with 1495 biochemical reactions and 40 % of total number of the reaction was the sum of the three largest subsystems; amino acid metabolism, carbohydrate metabolism, and metabolism of cofactors as well as vitamins. To investigate the connections between genome and phenome of P. marinum J15 and to validate the constructed GEM, BIOLOG Phenotype Microarray was performed. Also, DuctApe program was used in order to further analyse metabolic functionality of this bacterium. Main phenotype microarray (PM) assays showed that P. marinum J15 was able to use: i) 93 of the 190 carbon sources tested, where 61 were used efficiently, among which there were 16 amino acids; ii) 41 of the 95 nitrogen sources tested, where 22 compounds were used efficiently, among which were 9 amino acids and 8 peptides, and iii) 3 of the 94 phosphorous and sulphur sources tested. Furthermore, resistance to antibiotics, high tolerance to osmotic stress, to basic pH and to toxic compounds was revealed by PM. The complete genome, draft GEM and phenotypic data of P. marinum J15 in this study would be a resource for many subsequent studies of this genus, especially since there is only one published research on isolation of P. marinum AK15, but none on the genomic and phenotypic characteristic. This information will be essential for discovery of unique genes and secondary metabolite.